Negative impact of concurrent overexpression of MYC and BCL2 in patients with advanced diffuse large B-cell lymphoma treated with dose-intensified immunochemotherapy. Issue 12 (1st December 2016) - Takahashi, Hiromichi; Miura, Katsuhiro; Nakagawa, Masaru; Sugitani, Masahiko; Amano, Yusuke; Kurita, Daisuke; Sakagami, Masashi; Ohtake, Shimon; Uchino, Yoshihito; Kodaira, Hitomi; Iriyama, Noriyoshi; Kobayashi, Sumiko; et al.
Abstract: Co-expression of MYC and BCL2 proteins in diffuse large B-cell lymphoma (DLBCL), or 'double-expressor lymphoma' (DEL), results in poor patient prognosis, but the significance of DEL when aggressive treatments are applied remains uncertain. We performed a retrospective analysis of 40 patients with de novo DLBCL, who were categorized as being at high/high-intermediate risk according to the age-adjusted International Prognostic Index. Patients underwent an R-Double-CHOP regimen, a dose-intensified immunochemotherapy with or without consolidative high-dose chemotherapy followed by autologous stem cell transplantation. According to immunohistochemical analysis, 10 (25%) patients were categorized as having DEL, showing positivity for MYC (≥40%) and BCL2 (≥50%). The 3 year progression-free survival and overall survival of the DEL group were significantly worse compared with those of the non-DEL group (30% vs. 63%, p = 0.019 and 40% vs. 82%, p = 0.006, respectively). These results suggest that advanced DEL may need discrete treatment strategies.